How Shopping Mall Service Quality Affects Customer Loyalty Across Developing Countries: The Moderation of the Cultural Context. Issue 4 (December 2018) - Diallo, Mbaye Fall; Diop-Sall, Fatou; Djelassi, Souad; Godefroit-Winkel, Delphine
Cross-cultural studies indicate the importance of service quality and loyalty in different nations, but they do not specify how cultural context affects the relationships between such constructs. The current research investigates whether mall service quality and its specific dimensions affect loyalty, as well as how cultural contexts moderate the relationships between these constructs in three developing countries (Morocco, Senegal, and Tunisia). With a sample of 750 real customers, the authors show that mall service quality and its specific dimensions affect customer loyalty through the positive mediation of customer satisfaction and mall perceived value. Depending on the country, service quality dimensions (mall physical aspects, reliability, problem solving, and personnel attention) have distinct effects on customer loyalty. Furthermore, mall service quality drives customer loyalty positively in Morocco and Senegal. Customer satisfaction has a positive effect on customer loyalty in Senegal and Tunisia. Due to their different cultural contexts, these three developing countries do not exhibit a homogeneous pattern.